The Effect of Motivation on Employee Work Productivity at Regional Water Drinking Company (PDAM) Tirta Jeneberang Gowa District - Agustina, Indriani; Nurman; Musa, Chalid Imran; Burhanuddin; Natsir, Uhud Darmawan (International Humanity Advance, Business & Sciences, 2024)
The purpose of this study is to ascertain whether employee motivation influences their abilities to produce work-related results at the regional Drinking water Company (PDAM) Tirta Jeneberang, Gowa regency. Therewere 116 employee total who made up the population of this study. Utilizing stratified Random sampling, 54 samples werexused. Questionnaires were used in the approaches for gathering data. Quantitative descriptive analysis using the statistical Product and Service Solution (SPSS) was used for data analysis methodologies. Based on the study's findings, a straightforward linear analysis revealed that a constant value of 10,115 can be interpreted as meaning that if the motivational variable has a value of 0, then work productivity has increased by 10,115. Similarly, the positive beta coefficient on motivation (X) can be interpreted as meaning that for each unit of motivation that is increased, work productivity will rise by 0.703 as well. Work productivity increases by 0.703 points when motivation is taken into account. This demonstrates that efforts to boost the job efficiency of employees of the Tirta Jeneberang Regional Drinking Water Company (PDAM), Gowa Regency, depend greatly on their motivation.